Critical Analysis of Annex VI of MARPOL: Evaluating the Need for New Restriction Limits to Preserve the Ozone Layer - Sheikh Mehbuba Moitree (Law and Society Students' Journal)
MAPROL, the International Convention for the Prevention of Pollution from Ships is an essential instrument that addresses marine pollution, whereas Annex VI focuses specifically on combating and regulating the air pollution that is caused by ocean-going vessels. Annex VI’s strict regulation that governs Nitrogen Oxide (NOx) emissions and mandates using low-sulfur fuel to reduce the ozone-producing pollutants protects human health and environmental degradation. However, despite these efforts, challenges persist because, ocean-going vessels remain significant contributors to air pollution, emitting NOx, Sulfur Oxide (SOx), and other particular matters which directly or indirectly have dangerous and risky impact on human life and the ozone layer as well.